(untitled) (Social Science Review, 2025)
This article investigates the role and representation of the female characters in Rubaiyat Hossain’s critically acclaimed feminist film Under Construction (2015). This qualitative and explorative study uses textual analysis and approaches to representation by Stuart Hall as the methodology. This study deploys the concept of feminist political economy, women and economics, and subjectivity as the theoretical framework. Findings show that female characters in the film either adhered to traditional gender roles or were financially dependent on others. Hence, they were prone to being exploited by male-dominated systems due to their limited choices and lack of control. This study delves into the experiences of three women characters, examining their behavior in response to societal norms and the perceptions they encounter from others. Its goal is to grasp the fundamental concepts of feminist political economy, women and economics, and subjectivity to assess their relevance in contemporary society. Social Science Review, Vol. 41(1), June 2024, Page 73-90.